2023
DOI: 10.1001/jamanetworkopen.2023.0849
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sequential Intravesical Gemcitabine and Docetaxel vs Bacillus Calmette-Guérin for the Treatment of Patients With High-Risk Non–Muscle-Invasive Bladder Cancer

Abstract: ImportanceDue to the ongoing bacillus Calmette-Guérin (BCG) shortage, sequential intravesical gemcitabine and docetaxel has been increasingly used as first-line therapy for high-risk non–muscle-invasive bladder cancer (NMIBC). However, data directly comparing these 2 therapies are lacking.ObjectiveTo compare the outcomes of patients with high-risk NMIBC treated with gemcitabine and docetaxel vs BCG.Design, Setting, and ParticipantsThis retrospective cohort study was conducted from January 1, 2011, to December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 35 publications
0
42
0
Order By: Relevance
“…To achieve this goal, it is crucial to understand the most common complications associated with RARC to allow surgeons to take action to prevent their occurrence. To the best of our knowledge, only a few studies have evaluated the type of complications that may occur after RARC with intracorporeal neobladder, and the generalizability of their results is limited [1][2][3][4][5]. Previous studies have reported complications from small single-institution or single-surgeon series of patients who underwent RARC with either extracorporeal or intracorporeal neobladder, or did not use standardized criteria to report complications [6].…”
Section: Fundingmentioning
confidence: 99%
“…To achieve this goal, it is crucial to understand the most common complications associated with RARC to allow surgeons to take action to prevent their occurrence. To the best of our knowledge, only a few studies have evaluated the type of complications that may occur after RARC with intracorporeal neobladder, and the generalizability of their results is limited [1][2][3][4][5]. Previous studies have reported complications from small single-institution or single-surgeon series of patients who underwent RARC with either extracorporeal or intracorporeal neobladder, or did not use standardized criteria to report complications [6].…”
Section: Fundingmentioning
confidence: 99%
“…However, recent studies are demonstrating promising outcomes with the combination of two chemotherapeutic agents (gemcitabine and docetaxel) in the treatment of HR-NMIBC. 19,20 In a retrospective review, McElree et al 21 found 84% 2-year high-grade recurrence free survival (HG-RFS) using gemcitabine and docetaxel for BCG-naïve HR-NMIBC. Further long-term, retrospective analysis in a BCG-unresponsive cohort found a 75% 5-year bladder preservation rate, a 91% 5-year cancer-specific survival (CSS) rate, a 75% cystectomy free survival and, a 30% 5-year HG-RFS.…”
Section: Introductionmentioning
confidence: 99%
“…Several randomized controlled trials (RCTs) have shown that intravesical BCG therapy that includes an induction course of 6 weekly instillations and a maintenance course every 3–6 months for over 1–3 years is superior to TURBT alone 12‐16 or TURBT followed by intravesical induction chemotherapy 15,17,18 in terms of recurrence and progression prevention in NMIBC patients. However, recent studies are demonstrating promising outcomes with the combination of two chemotherapeutic agents (gemcitabine and docetaxel) in the treatment of HR‐NMIBC 19,20 . In a retrospective review, McElree et al 21 .…”
Section: Introductionmentioning
confidence: 99%
“…8 To perform a direct comparison with BCG, we recently published a retrospective report of 312 patients with newly diagnosed high-risk NMIBC, of whom 138 received Gem/Doce and 174 received BCG. 9 Patients who received Gem/Doce were older (median age 74 vs 71 years, P [ .002), but all clinicopathological features were similar between treatment groups. Gem/ Doce yielded superior 2-year HG-RFS compared to BCG (81% vs 69%), with no impact of clinicopathological features on recurrence on multivariable analysis.…”
mentioning
confidence: 98%